Connecticut Yankees in Kansas - Michael Stubbs (Symphony in the Flint Hills, 2011)
Those of us who took Kansas or Missouri history classes may remember reading about Bleeding Kansas. This is the term used to describe the series of events that occurred after the creation of Nebraska and Kansas Territories in 1854. These events are now seen as the prelude to the Civil War.
Keywords: Bleeding Kansas; rifle; church; Beecher bible; Henry Ward Beecher